Prepuberal stimulation of 5-HT7-R by LP-211 in a rat model of hyper-activity and attention-deficit: permanent effects on attention, brain amino acids and synaptic markers in the fronto-striatal interface. - Lucia A Ruocco; Concetta Treno; Ugo A Gironi Carnevale; Claudio Arra; Gianpiero Boatto; Maria Nieddu; Cristina Pagano; Placido Illiano; Fabiana Barbato; Angela Tino; Ezio Carboni; Giovanni Laviola; et al. (PLoS ONE)
The cross-talk at the prefronto-striatal interface involves excitatory amino acids, different receptors, transducers and modulators. We investigated long-term effects of a prepuberal, subchronic 5-HT7-R agonist (LP-211) on adult behaviour, amino acids and synaptic markers in a model for Attention-Deficit/Hyperactivity Disorder (ADHD). Naples High Excitability rats (NHE) and their Random Bred controls (NRB) were daily treated with LP-211 in the 5th and 6th postnatal week. One month after treatment, these rats were tested for indices of activity, non selective (NSA), selective spatial attention (SSA) and emotionality. The quantity of L-Glutamate (L-Glu), L-Aspartate (L-Asp) and L-Leucine (L-Leu), dopamine transporter (DAT), NMDAR1 subunit and CAMKIIα, were assessed in prefrontal cortex (PFC), dorsal (DS) and ventral striatum (VS), for their role in synaptic transmission, neural plasticity and information processing. Prepuberal LP-211 (at lower dose) reduced horizontal activity and (at higher dose) increased SSA, only for NHE but not in NRB rats. Prepuberal LP-211 increased, in NHE rats, L-Glu in the PFC and L-Asp in the VS (at 0.250 mg/kg dose), whereas (at 0.125 mg/kg dose) it decreased L-Glu and L-Asp in the DS. The L-Glu was decreased, at 0.125 mg/kg, only in the VS of NRB rats. The DAT levels were decreased with the 0.125 mg/kg dose (in the PFC), and increased with the 0.250 mg/kg dose (in the VS), significantly for NHE rats. The basal NMDAR1 level was higher in the PFC of NHE than NRB rats; LP-211 treatment (at 0.125 mg/kg dose) decreased NMDAR1 in the VS of NRB rats. This study represents a starting point about the impact of developmental 5-HT7-R activation on neuro-physiology of attentive processes, executive functions and their neural substrates.